2008
DOI: 10.1111/j.1742-6723.2008.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Leaving the emergency department without being seen

Abstract: Patients who leave the ED without being seen (LWBS) are unlikely to be satisfied with the quality of the service provided and might be at risk from conditions that have not been assessed or treated. We therefore examined the available research literature to inform the following questions: (i) In patients who attend for ED care, what factors are associated with the decision to LWBS? (ii) In patients who attend for ED care, are there adverse health outcomes associated with the decision to LWBS? (iii) Which inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 27 publications
9
85
3
4
Order By: Relevance
“…A literature review concluded in 2008 that ''patients generally have very low rates of subsequent admission, and reports of serious adverse events are rare.'' 14 This may explain why some settings tolerate higher LWBS proportions. No study has evaluated predictive factors associated with an unfavourable outcome for children who LWBS.…”
Section: Ré Sumémentioning
confidence: 99%
“…A literature review concluded in 2008 that ''patients generally have very low rates of subsequent admission, and reports of serious adverse events are rare.'' 14 This may explain why some settings tolerate higher LWBS proportions. No study has evaluated predictive factors associated with an unfavourable outcome for children who LWBS.…”
Section: Ré Sumémentioning
confidence: 99%
“…9,10 Patients who leave the ED without being seen are equally likely as those who were assessed and treated to seek follow-up care. 11 Our study found no difference in T 1 or total LOS between PGY-1 and PGY-2 residents.…”
Section: Discussionmentioning
confidence: 99%
“…13,[35][36][37][38] La littérature internationale suggère plutôt des taux entre 0,06% et 20%. 5,7,9,10,16,17,20,24,28,29,32,33,39,40 Aussi, la durée moyenne de séjour dans les urgences au Québec est comparable à celle de notre étude soit de 8h16 min globalement et 16h43 pour les patients sur civières. 41 Cette étude rétrospective a permis de dresser un portrait des facteurs démographiques, cliniques et hospitaliers ayant un impact sur le nombre de DAPCM, pour les deux salles d'urgence du CHUS.…”
Section: Discussionunclassified
“…[5][6][7]27,30,43 Parmi les patients avec un code de triage de V, 27,5% (HF) et 34,2% (HD) ont fait un DAPCM. Par contre, la majorité (60%) des cas de DAPCM dans notre étude sont des patients ayant un code de triage de IV.…”
Section: Discussionunclassified
See 1 more Smart Citation